Examining the Effects of Technical Indicators, Fundamental Factors, and Market Sentiment on Forex Trading Behavior at YI Trade - I Gusti Agung Widi Pradipta; Ni Made Suci; Fridayana Yudiatmaja (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Forex trading carries various risks that require attention. Based on this, this study aims to analyze the factors influencing the selection of forex trading transaction recommendations on YI Trade. This research is quantitative with a descriptive quantitative approach. The population includes community members, platform users, or customers receiving YI Trade online trading signals. The research sample was selected using a purposive sampling technique. The sample size in this study ranged from 50 to 79 respondents. The research method used in this study was a closed-ended questionnaire. The data collection instrument used a questionnaire sheet. The techniques used in data analysis were multiple linear regression and the t-test. The results showed that, first, testing the influence of Fundamentals (X1) on Transaction Recommendations (Y) obtained a coefficient value of 0.198 with a significance value of 0.014, indicating a significant influence between Fundamentals (X1) and Transaction Recommendations (Y). Second, the influence of Perception of Technical Analysis (X2) on Transaction Recommendation (Y) obtained a coefficient value of 0.426 with a significance value of 0.000, so there is a significant influence of Perception of Technical Analysis (X2) on Transaction Recommendation (Y). Third, the influence of Market Sentiment (X3) on Transaction Recommendation (Y) obtained a coefficient value of 0.098 with a significance value of 0.025, so there is a significant influence of Market Sentiment (X3) on Transaction Recommendation (Y). Fourth, Hypothesis VI. significance value of 0.000 (α <0.05). It is concluded that the Fundamental variables (X1), Perception of Technical Analysis (X2), and Market Sentiment (X3) simultaneously have a significant influence on the Transaction Recommendation variable (Y).